New technologies in global societies - Luo, Peilin; Fortunati, Leopoldina; Yang, Shanhua (World Scientific, 2006)
Technological advancements in the West since the last millennium have contributed to global modernity. Technologies set conditions for the closeness of the nation-states and for the affinity of the global and the local. They are also penetrating everyday life, and even sometimes the body, producing radical social changes. Yet, arguing that new technologies bring a new life and a promising future to global societies remains a questionable thesis. This book attempts to explore the relationship between new technologies and global societies, to gain an understanding of how the positive as well as.